Determinants influencing level of awareness towards cash waqf among Kota Tinggi residents / Muhammad Naqiuddin Norazman - Norazman, Muhammad Naqiuddin (Faculty of Business and Management, 2019)
Cash waqf is one of the instruments that have that the purpose wants to attract and encourage more individuals to take a part in this waqf. This study provides information regarding the level of awareness towards cash waqf among Kota Tinggi residents. It helps the waqf institutions that manage all the funds of waqf that influencing level of awareness towards cash waqf. This study also to determine the factors that influencing the awareness of cash waqf in Kota Tinggi. The objective of this study is to identify the relationship between the selected data on the level awareness towards cash waqf which is the three independent variables such as religion obligation, subjective norm and knowledge. The data was collected by using SPSS software. This study conducted through primary data which is using questionnaire and secondary data which is from the past research. The questionnaire was distributed among Kota Tinggi residents.